Water Evaporation Induced Conversion of CuSe Nanoflakes to Cu2−xSe Hierarchical Columnar Superstructures for High‐Performance Solar Cell Applications. (7th April 2015) - Xu, Jun; Yang, Qingdan; Kang, Wenpei; Huang, Xing; Wu, Chunyan; Wang, Li; Luo, Linbao; Zhang, Wenjun; Lee, Chun‐Sing
<x xml:space="preserve">Abstract</x> In this work, a facile and low‐temperature water evaporation approach to prepare columnar superstructures consisting of face centered cubic (fcc) Cu2−xSe nanoflakes stacked along 〈111〉 direction is reported. Formation of such unique stacked nanoflake assemblies is resulted from oriented attachment of isolated hexagonal CuSe nanoflakes along the 〈001〉 direction with a ripening effect driven by solvent evaporation, and then followed by a phase conversion into fcc Cu2−xSe. Evolution from hexagonal CuSe nanoflakes to fcc Cu2−xSe columnar superstructures results in obvious red‐shift of band‐gap absorption edge from 670 to 786 nm and dramatically decreased Raman resonance band intensity of the Se–Se stretching mode at 259 cm−1 due to the phase conversion and composition variation. Remarkably, the Cu2−xSe columnar superstructures are employed as low‐cost and highly efficient counter electrodes (CEs) in quantum dot sensitized solar cells, exhibiting excellent electrocatalytic activity for polysulfide electrolyte regeneration. A ZnSe/CdSe cosensitized solar cell using the Cu2−xSe CE shows a significant increase in fill factor and short‐current density (JSC) and yields a 128% enhancement in power conversion efficiency as compared to the traditional noble metal Pt CE.